MUHAMMAD UTHMAN EL-MUHAMMADY: ANALISIS SUMBANGANNYA DALAM PENULISAN (Muhammad Uthman El-Muhammady: Analysis on His Contribution to Writing) - Ali Mat Zin, Aizan; Aziz, Siti Hajar (Journal of Al-Tamaddun, 2018)
This article studies biography of Muhammad Uthman El-Muhammady by exploring historical phases of his life from educational bedrock to career pathway. Method of documentation were used to gather data on his biography, writtings and authorship in addition to method of interview. Data were analysed by inductive, deductive, comparative and content analyses. Findings exhibit his contributions to writing are indisputable and significant in religious matters and thinking. This study is qualitative yet generated quantitative data which is presented in table, graft and pie chart. In conclusion, his contributions proved that he had prolonged the tradition of inheriting knowledge through the medium of writing by previous Muslim scholars, towards 21st Century.